Interconnected three-dimensional V2O5/polypyrrole network nanostructures for high performance solid-state supercapacitors. Issue 2 (27th November 2014) - Qian, Tao; Xu, Na; Zhou, Jinqiu; Yang, Tingzhou; Liu, Xuejun; Shen, Xiaowei; Liang, Jiaqi; Yan, Chenglin
Abstract : We report all-solid-state supercapacitors based on interconnected three-dimensional V2 O5 /polypyrrole network nanostructures with enhanced pseudocapacitive performance. Abstract : Supercapacitor electrodes composed of a 3D V2 O5 network with polypyrrole (PPy) uniformly decorated onto each nanowire were fabricated to enhance their pseudocapacitive performance. The continuous 3D network creates channels for better ion transport, and the high degree of pore connectivity in the network enhances the mass transport. The PPy shell could enhance the electric conductivity and prevent the dissolution of vanadium. These merits together with the ideal synergy between V2 O5 and PPy lead to a high specific capacitance of 448 F g −1, which is three times higher than that of the stacked V2 O5 . The all-solid-state symmetric supercapacitor device assembled by the V2 O5 /PPy core/shell 3D network exhibits a high energy density (14.2 W h kg −1 ) at a power density of 250 W kg −1 and good cyclic stability (capacitance retention of 81% after 1000 cycles). Furthermore, the prepared device could power a red light-emitting diode indicator efficiently after charging for only 10 s.